A Case Study On DRB-Hicom Bhd In The Automotive Industry - Chen, Lu Shen (2005)
DRB-Hicom has undertaken many strategic moves to maintain its lead in the automotive sector. This paper is a study on the strategic management of DRB-HICOM Berhad where presented in two segments.